2019
DOI: 10.1016/j.jallcom.2019.02.238
|View full text |Cite
|
Sign up to set email alerts
|

Cavitation erosion performance of CrAlYN/CrN nanoscale multilayer coatings deposited on Ti6Al4V by HIPIMS

Abstract: Water droplet erosion (WDE) protection of Ti6Al4V turbofan blades is of paramount importance to the aviation industry. A novel CrAlYN/CrN nanoscale multilayer coating deposited by the HIPIMS technique was evaluated as a potential candidate for this application. Literature suggests a strong correlation in performance ranking under WDE and cavitation erosion (CE) tests. Hence, the WDE performance of the CrAlYN/CrN coating on Ti6Al4V was investigated with an ultrasonic cavitation device. The results show excellen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…The decrease in cumulative volume loss caused by PVD coating was noted in many works, e.g., in References [77,[80][81][82]. However, some studies showed that the deposition of a hard PVD coating does not always provide extended incubation time and/or improved resistance to cavitation damage [46,67,79,83]. The 2.7 µm thick TiN coating deposited on Ti6Al4V alloy had no incubation period and a very high erosion rate compared to the uncoated substrate (Figure 4a) [67].…”
Section: Resistance Of Pvd Coatings To Cavitation Erosionmentioning
confidence: 89%
See 2 more Smart Citations
“…The decrease in cumulative volume loss caused by PVD coating was noted in many works, e.g., in References [77,[80][81][82]. However, some studies showed that the deposition of a hard PVD coating does not always provide extended incubation time and/or improved resistance to cavitation damage [46,67,79,83]. The 2.7 µm thick TiN coating deposited on Ti6Al4V alloy had no incubation period and a very high erosion rate compared to the uncoated substrate (Figure 4a) [67].…”
Section: Resistance Of Pvd Coatings To Cavitation Erosionmentioning
confidence: 89%
“…The phenomenon of cavitation erosion consists in the degradation of the material surface as a result of multiple impacts of micro-jets formed during the implosions of cavitation bubbles. Cavitation erosion resistance of materials is tested using mainly ultrasonic devices compliant with the ASTM G-32 standard (Figure 1) [30,53,[65][66][67][68][69]. The ASTM G-32 standard allows performing tests in the direct and indirect methods (Figure 1).…”
Section: Resistance Of Pvd Coatings To Cavitation Erosionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, the differences in the corrosion resistance of the coating and the substrate, as well as the decrease in hardness and modulus of elasticity under cyclic loading conditions, affect the development of damage. Although the high hardness of the coating protects against cavitation degradation, a large difference in the hardness of the coating and the substrate can lead to accelerated erosion through delamination and removal of the coating [ 28 , 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…The different performance of the five coatings may be caused by the following two factors. Firstly, the micro defects of the coatings such as pores, cracks, unmelted, or semi-melted particles play a negative role in cavitation erosion process [31][32][33][34]. It is clearly observed from Figure 9 that microcracks, pores, and unmelted that particles existed in the surface of the HT 1100 coating before cavitation erosion.…”
Section: Porosity and Microhardnessmentioning
confidence: 98%